Ice investigations at the Nanisivik wharf: an historical retrospective - Frederking, Robert (IAHR, 2022)
The wharf at Nanisivik was constructed over the winter 1974-75. It was the first deep-water wharf in the Canadian Arctic and there were questions on ice-structure interaction processes, ice loading and performance. This provided the impetus for a series of investigations at the site extending up to the present time. The wharf is located on Strathcona Sound, which is characterized by relatively land fast ice subject to vertical motions under tidal action. The nearby community and mine provided access and logistics which were very amenable for extensive on-site investigation. Early investigations extending over several winters showed the build-up of a zone of ice between the vertical wharf face and the adjacent level ice sheet. This ice behavior extends to the present. Various schemes of ice force measurement, directly on the wharf face and in the adjacent ice cover have been conducted and reported on at various conferences. Because of the mine, which the wharf was built to serve, extended season marine shipping occurred and also played a part in the ice investigations. This paper will provide an overview of ice investigations conducted at and around the Nanisivik wharf over an almost 50-year period and a summary of what has been learned. Peer reviewed: Yes NRC publication: Yes